(untitled) (Research, Society and Development, 2025)
Introduction: Childhood asthma is a chronic respiratory disease that affects millions of children worldwide and represents a major public health challenge. It is characterized by airway inflammation, mainly mediated by cytokines, with exaggerated activation of innate immunity. Factors such as genetic predisposition, environmental exposure, and maternal smoking contribute to the imbalance between Th1 and Th2 helper T cells, leading to increased vascular permeability, mucus hypersecretion, bronchial hyperresponsiveness, and bronchoconstriction. Understanding these mechanisms is essential for effective disease management. Objective: This study aimed to analyze the interaction between immune response and oxidative stress in childhood asthma, as well as to identify relevant biomarkers and new therapeutic strategies. Methodology: A descriptive narrative review was conducted based on research from PubMed and Google Scholar, including 21 studies published between 2011 and 2025. Results: The interaction between environmental stressors and the airway epithelial barrier plays a critical role in the immunological response of asthma. Biomarkers such as CRTH2 and eosinophil count in sputum have proven useful in assessing disease severity. Th1 and Th2 cytokines have been implicated in asthma exacerbations, highlighting the immunological complexity of the disease. Conclusion: Although advances such as FeNO measurement and biological therapies have improved asthma management, challenges remain, particularly in treating non-Th2 phenotypes, emphasizing the need for more individualized approaches.